Games Hospitals Play: Entry Deterrence in Hospital Procedure Markets - Dafny, Leemore S. (Journal of economics & management strategy, 2005)
Strategic investment models, though popular in the theoretical literature, have rarely been tested empirically. This paper develops a model of strategic investment in inpatient procedure markets, which are well‐suited to empirical tests of this behavior. Potential entrants are easy to identify in such markets, enabling the researcher to accurately estimate the entry threat faced by different incumbents. I derive straightforward empirical tests of entry deterrence from a model of patient demand, procedure quality, and differentiated product competition. Using hospital data on electrophysiological studies, an invasive cardiac procedure, I find evidence of entry‐deterring investment. These findings suggest that competitive motivations play a role in treatment decisions.